2022
DOI: 10.31234/osf.io/vzh4g
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating the performance of markerless prospective motion correction and selective reacquisition in a general clinical protocol for brain MRI

Abstract: Objective: Head motion is one of the most common sources of artefacts in brain MRI. When imaging young children, general anaesthesia is common, which is a limited resource. We evaluate the performance of markerless prospective motion correction (PMC) and selective reacquisition in a complete clinical protocol for brain MRI, comparing acquisitions with and without instructed intentional head motion.Materials and Methods: Image quality metrics and ratings were analysed for scans with and without PMC - acquired w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…What's more, when it came to motion, we had to rely on previously used parameters (Loizillon et al, 2023(Loizillon et al, , 2024 since we could not find a reliable metric that did not require a reference image to quantify the amount of motion in a given MRI. Despite the recent efforts led by Eichhorn et al (2022) to find metrics that best correlate with radiological assessment, such as the average edge strength and Tenengrad measure, so far none of them have proven their robustness to other types of artefacts and in particular different types of contrast severity, leaving motion quantification as an open question.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…What's more, when it came to motion, we had to rely on previously used parameters (Loizillon et al, 2023(Loizillon et al, , 2024 since we could not find a reliable metric that did not require a reference image to quantify the amount of motion in a given MRI. Despite the recent efforts led by Eichhorn et al (2022) to find metrics that best correlate with radiological assessment, such as the average edge strength and Tenengrad measure, so far none of them have proven their robustness to other types of artefacts and in particular different types of contrast severity, leaving motion quantification as an open question.…”
Section: Discussionmentioning
confidence: 99%
“…For noise simulation, we explored various standard deviation (σ) ranges to find optimal parameters for corrupting MRIs with moderate and severe noise: σ = {[0, 10]; [5,15]; [10,20]; [15,25]; [20,30] Regarding motion artefacts, there is still no robust metric in the literature to quantify the motion present in MRIs. Recently, Eichhorn et al (2022) have shown that SSIM and PSNR were the metrics that correlate best with radiological assessment. What's more, they relied on the evaluation of pixel-by-pixel differences between images and were therefore very sensitive to misregistration between the original image and the corrupted image (Reguig et al, 2022).…”
Section: Artefact Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The coil sentitivity maps were kept unchanged. We used 524 rigid‐body head motion patterns acquired on a scanner with an optical tracking system from a study where participants were instructed to perform shaking or nodding motion 22 . 393 patterns were used for training and 131 for validation.…”
Section: Methodsmentioning
confidence: 99%
“…We used 524 rigid-body head motion patterns acquired on a scanner with an optical tracking system from a study where participants were instructed to perform shaking or nodding motion. 22 393 patterns were used for training and 131 for validation. We multiplied each measured motion pattern by a uniformly randomly selected factor between 0 and 2 in order to generate a variety of training images with different amounts of motion.…”
Section: Synthesizing Motion-corrupted K-space Datamentioning
confidence: 99%